2017
DOI: 10.1002/ejoc.201700661
|View full text |Cite
|
Sign up to set email alerts
|

Selective Trifluoromethylthiolation and Trifluoromethylsulfinylation of Indoles with Sodium Trifluoromethanesulfinate Promoted by Phosphorus Reagents

Abstract: Direct trifluoromethylthiolation and trifluoromethylsulfinylation reactions by using sodium trifluoromethanesulfinate were promoted by different phosphorus reagents to selectively occur under mild and transition‐metal‐free conditions. In the presence of phosphorus trichloride, sodium trifluoromethanesulfinate readily underwent a reaction with indole and its derivatives in N,N‐dimethylformamide (DMF) at room temperature to give 3‐trifluoromethylthiolated products in good yields. Trifluoromethylsulfinylation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Different phosphorus reductive reagents were evaluated by Liu, Lin and co-workers. It was found that phosphorus trichloride (PCl 3 ) allowed to react with CF 3 SO 2 Na and a series of indoles afforded the corresponding 3-CF 3 S derivatives selectively in good to excellent yields ( Scheme 74 ) [ 101 ]. Unlike the work of Cai using PPh 3 and N -chlorophthalimide, here, PCl 3 was used both as a reducing and chlorinating reagent.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Different phosphorus reductive reagents were evaluated by Liu, Lin and co-workers. It was found that phosphorus trichloride (PCl 3 ) allowed to react with CF 3 SO 2 Na and a series of indoles afforded the corresponding 3-CF 3 S derivatives selectively in good to excellent yields ( Scheme 74 ) [ 101 ]. Unlike the work of Cai using PPh 3 and N -chlorophthalimide, here, PCl 3 was used both as a reducing and chlorinating reagent.…”
Section: Reviewmentioning
confidence: 99%
“…After these initial works, it is only in 2017 that new results using CF 3 SO 2 Na appeared in the field. As briefly mentioned in the preceding section, Liu, Lin and co-workers evaluated different phosphorus reductive reagents and found that PCl 3 (3 equiv) afforded the corresponding 3-CF 3 S derivatives whereas P(O)Cl 3 (1 equiv) allowed to get selectively the trifluoromethylsulfinyl derivatives 90 ( Scheme 80 ) [ 101 ].…”
Section: Reviewmentioning
confidence: 99%
“…The versatile reactivity of sodium trifluoromethane-sulfinate was observed by using different phosphorus reagents, such as phosphorus trichloride (PCl 3 ) and phosphorus oxychloride (POCl 3 ) in DMF at room temperature ( Table 8 ). 87 By using PCl 3 reagent the trifluoromethylthiolation of indole derivatives gave 3-trifluoromethylthiolated indoles in moderate to good yields, whereas the corresponding sulfoxides were delivered in good to high yields in the presence of phosphorus oxychloride. Moreover, this protocol was extended to other sodium perfluoroalkanesulfinates to obtain the corresponding products in high yields.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…Shortly after, Cai and co-workers discovered that PPh 3 was able to reduce CF 3 SO 2 Na, in the presence of stoichiometric N -chlorophthalimide (NCS), to generate in situ CF 3 SCl, which was subsequently reacted with indoles and pyrroles efficiently (Scheme B) . In addition, other phosphorus compounds such as PCl 3 , P­(O)­Cl 3 , or P­(O)­Br 3 could also convert CF 3 SO 2 Na to generate active electrophilic trifluoromethylthiolating intermediate. …”
Section: Friedel–crafts Trifluoromethylthiolation With Reagent 15 And...mentioning
confidence: 99%